Hadith Perspectives on Labor Welfare: The Principle of Compensation for Effort - Amirul Haq, Ichsan; Hawari, Rafif; Muhamad Ashoni, Akbar; Nusantara, Zamzani (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
The issue of worker welfare and fair compensation is becoming increasingly important in the modern world of work. Islamic values, especially those contained in the hadith, provide ethical guidance in creating fair labor practices. The hadith of the Prophet Muhammad PBUH which reads “Give wages to workers before their sweat dries” emphasizes the importance of timely payment of wages as a form of respect for workers' rights and prevention of exploitation. This research aims to explore the application of Islamic principles related to wage justice and the protection of workers' rights, focusing on the contemporary context where late payment of wages is still a significant problem. A qualitative approach is used to analyze relevant hadiths and interpretations of scholars, as well as to review literature and case studies to understand the impact of wage payments on workers' welfare. The findings show that timely payment of wages not only reflects fairness, but also contributes to workers' financial well-being, preserves their dignity, and increases satisfaction and productivity. Compliance with the principle of fair wage distribution also encourages the creation of a positive and harmonious work culture. The study concludes that Islamic principles of justice and welfare are universal and relevant to address the challenges of modern employment. The application of these principles can create mutually beneficial working relationships and support the formation of a more just and prosperous society